Bioactive glass (BG) ICIE16 shows promising osteogenic properties compared to crystallized 45S5-BG - Westhauser, Fabian; Hohenbild, Frederike; Arango-Ospina, Marcela; Schmitz, Sarah I.; Wilkesmann, Sebastian; Hupa, Leena; Moghaddam-Alvandi, Arash; Boccaccini, Aldo R. (International journal of molecular sciences, 2020)
The ICIE16-bioactive glass (BG) (48.0 SiO2, 6.6 Na2O, 32.9 CaO, 2.5 P2O5, 10.0 K2O (wt %)) has been developed as an alternative to 45S5-BG, the original BG composition (45.0 SiO2, 24.5 Na2O, 24.5 CaO, 6.0 P2O5 (wt %)), with the intention of broadening the BG sintering window while maintaining bioactivity. Because there is a lack of reports on ICIE16-BG biological properties, the influence of ICIE16-BG on viability, proliferation, and osteogenic differentiation of human mesenchymal stromal cells (MSCs) was evaluated in direct comparison to 45S5-BG in this study. The BGs underwent heat treatment similar to that which is required in order to fabricate scaffolds by sintering, which resulted in crystallization of 45S5-BG (45S5-CBG) while ICIE16 remained amorphous. Granules based on both BGs were biocompatible, but ICIE16-BG was less harmful to cell viability, most likely due to a more pronounced pH alkalization in the 45S5-CBG group. ICIE16-BG outperformed 45S5-CBG in terms of osteogenic differentiation at the cellular level, as determined by the increased activity of alkaline phosphatase. However, granules from both BGs were comparable regarding the stimulation of expression levels of genes encoding for osseous extracellular matrix (ECM) proteins. The addition of therapeutically active ions to ICIE16-BG might further improve its ability to stimulate ECM production and should be investigated in upcoming studies.